2022
DOI: 10.1002/cbdv.202100964
|View full text |Cite
|
Sign up to set email alerts
|

Rational Design, Synthesis, in Vitro, and in Silico Studies of Chlorophenylquinazolin‐4(3H)‐One Containing Different Aryl Acetohydrazides as Tyrosinase Inhibitors

Abstract: Tyrosinase plays a pivotal role in the hyperpigmentation and enzymatic browning of fruit and vegetable. Therefore, tyrosinase inhibitors can be of interest in industries as depigmentation compounds as well as anti‐browning agents. In the present study, a series of chlorophenylquinazolin‐4(3H)‐one derivative were rationally designed and synthesized. The formation of target compounds was confirmed by spectral characterization techniques such as IR, 1H‐NMR, 13C‐NMR, and elemental analysis. Among the synthesized d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Iraji and co-workers designed and synthesized a series of chlorophenylquinazolin-4(3H)-one derivatives (84, Figure 54) containing various aryl acetohydrazides as potential TYRIs [99]. The percentage of TYR inhibition resulted between 63.48 and 1.02%.…”
Section: Quinazolinesmentioning
confidence: 99%
“…Iraji and co-workers designed and synthesized a series of chlorophenylquinazolin-4(3H)-one derivatives (84, Figure 54) containing various aryl acetohydrazides as potential TYRIs [99]. The percentage of TYR inhibition resulted between 63.48 and 1.02%.…”
Section: Quinazolinesmentioning
confidence: 99%
“…4 So far, several natural and synthetic inhibitors for tyrosinase enzymes have been identied. [5][6][7][8] The studies showed that the compounds can inhibit tyrosinase enzyme in several different ways, including reduction of dopaquinone to dopa (ascorbic acid), 9 reduction of the amount of dopaquinone (thiol analogs), 10 and much greater affinity to tyrosinase enzyme compared to the main substrate (phenolic compounds). 11 Also, the alteration in the shape of the active site of the enzyme, such as compounds with acidic or basic properties, 12 the inactivation of the enzyme through the covalent bond with the enzyme, and irreversible inhibition of the enzyme, 13 and nally, the occupation of the active site and reversible inhibition of the enzyme 14 are the other mechanisms of tyrosinase inhibition.…”
Section: Introductionmentioning
confidence: 99%
“…Melanin produced by melanocytes is responsible for the pigmentation of skin, hair, and eyes and plays an important role in protecting human skin from the destructive effect of UV radiation and oxidative stress []. However, excessive melanin synthesis can cause abnormal pigmentation, age spots, freckles, and induce skin diseases as well as malignant melanoma [ 1 ]. Tyrosinase (EC 1.14.18.1, TYR) is metalloenzyme with six histidine residues and two conserved copper ions in its active site, which is essential for the catalytic activity of tyrosinase [ 2 ].…”
Section: Introductionmentioning
confidence: 99%